Co-producing development : participation, power and conflict in the upgrading of informal settlements in Nairobi - Rigon, Andrea (Trinity College (Dublin, Ireland). Department of Sociology, 2013)
This thesis analyses how social and political conflicts among different social actors shape the implementation of slum-upgrading programmes. The research focuses on the first two years (2008-2010) of the implementation of an internationally-funded slum-upgrading programme in Nairobi. In particular, the thesis explores the internal dynamics of the residents of one slum settlement and how they interact with the development programme and with the complex range of actors involved. The actor-oriented approach constitutes the main theoretical framework of this research. Mid-level theories from the sociology and anthropology of development are also employed to illuminate specific data. The thesis draws upon the body of work classified under the broad notion of a 'new ethnography of development’, a body of work which has so far predominantly focused on rural projects. The perspective offered by these works can also provide useful insights and tools to examine dispersed and multi-level agency in urban development programmes. Adopting an actor-oriented approach, this thesis analyses the 'co- production of development’ accomplished through negotiations, renegotiations, alliances, and conflict among different actors at multiple levels, and within a wider historical, political and policy context.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin